FACTORES SOCIALES QUE INCIDEN EN EL RENDIMIENTO ACÁDEMICO Y FRACASO ESCOLAR EN LOS ESTUDIANTES DE LA ESCUELA ZOILA MARÍA ASTUDILLO CELI DE LA CIUDAD DE LOJA Y EL ROL DEL TRABAJADOR SOCIAL. - Bravo Quezada, Tatiana del Cisne (2015)
The low academic performance is the limitation in the use of the knowledge acquired in the process of learning, as we understand the difficulty that the candidate submits in the different areas of study, expressing disinterest to learn, which can leave scars in their development and can affect your quality of life, the problem under study is: "The low academic performance in students of the school Zoila Maria Astudillo Celi". This research work has been developed through the General Objective To contribute to raise the academic performance, which will decrease the school failure of students of the school Zoila Maria Astudillo Celi". And also taking into account the specific objectives that were to know what are the social factors affecting the school failure; involve parents to the teaching-learning process of their children, put forward a proposal to improve the academic performance of students of the school Zoila Maria Astudillo Celi. In the present research used the methodology of the abstract to the concrete through the model of intervention in reality : first phase: the phase sensitive. second phase: the phase of technical information, third phase: research participant, fourth phase of determination. . The main findings of the research helped determine that the educational institution Zoila Maria Astudillo Celi most of the students presented low academic performance, is mainly because they come from single-parent family, the family environment where the child lives or girl is not appropriate, family problems, inadequate communication the low participation of parents in the education of their children. 5 At the end of the present research work is reached to the formulations of conclusions with their respective Recommendation, and also the design of a proposal for action that will help raise the academic performance.